Effects of a strength-training program for shoulder complaint prevention in female team handball athletes. A pilot study - Osteras, H.; Sommervold, M.; Skjoelberg, A. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: Very little is known about the potential for preventing the prevalence of shoulder complaints in handball players, particularly younger players. The aim of the present pilot study was to evaluate shoulder-strengthening program on shoulder complaints during a season of team handball.